Identification and Quantification of Necroptosis Landscape on Therapy and Prognosis in Kidney Renal Clear Cell Carcinoma - Xin, Sheng; Mao, Jiaquan; Duan, Chen; Wang, Jiaxin; Lu, Yuchao; Yang, Jun; Hu, Jia; Liu, Xiaming; Guan, Wei; Wang, Tao; Wang, Shaogang; Liu, Jihong; et al. (Frontiers in Genetics, 2022)
Kidney renal clear cell carcinoma (KIRC) has a high morbidity and gradually increases in recent years, and the rate of progression once relapsed is high. At present, owing to the lack of effective prognosis predicted marker and post-recurrence drug selection guidelines, the prognosis of KIRC patients is greatly affected. Necroptosis is a regulated form of cell necrosis in a way that is independent of caspase. Induced necroptosis is considered to be an effective strategy in chemotherapy and targeted drugs, and it also can be used to improve the efficacy of immunotherapy. Herein, we quantified the necroptosis landscape of KIRC patients from the Cancer Genome Atlas (TCGA) database and divided them into two distinct necroptosis-related patterns (C1, C2) through non-negative matrix factorization (NMF) algorithm. Multi-analysis revealed the differences in clinicopathological characteristics and tumor immune microenvironment (TIME) between them. Then we constructed the NRG prognosis signature (NRGscore) by stepwise COX regression analysis, including 10 NRGs (PLK1, APP, TNFRSF21, CXCL8, MYCN, TNFRSF1A, TRAF2, HSP90AA1, STUB1 and FLT3). We confirmed that NRGscore could be used as an independent prognostic marker for KIRC patinets and performed excellent stability and accuracy. A nomogram model was also established to provide a more beneficial prognostic indicator for the clinic. We found that NRGscore was significantly correlated with clinicopathological characteristics, TIME and tumor mutation burden (TMB) of KIRC patients. Moreover, NRGscore had effective guiding significance for immunotherapy, chemotherapy and targeted drugs.